2017
DOI: 10.1016/j.eurpsy.2017.01.1754
|View full text |Cite
|
Sign up to set email alerts
|

Elevated neutrophil lymphocyte ratio in patients with substance use disorders

Abstract: IntroductionDisturbances in inflammatory processes may play a role in the pathophysiology of psychiatric disorders. The neutrophil lymphocyte ratio (NLR) and C-reactive protein (CRP) are indicators of the systemic inflammatory response.ObjectivesThe current study was prepared based on the assumption that dysregulated immune function and elevated inflammation markers may be seen in substance use disorders.AimsOur aim was to investigate whether NLR and CRP are higher in patients diagnosed with substance use diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
3
0
5
Order By: Relevance
“…A recent study showed that half of FEP patients had co‐occurring substance use disorders, and substance use has been repeatedly reported to contribute to the development of psychosis with adverse outcomes (Brunette et al, 2018; Kraan et al, 2016; Schoeler et al, 2016). Similarly, there are some reports that support the hypothesis that inflammatory pathways might be related to substance use disorders (Ozkan et al, 2017; Uys, Mulholland, & Townsend, 2014; Womersley, Townsend, Kalivas, & Uys, 2019). Considering previous findings that support the involvement of inflammatory pathways in both psychosis and substance‐related disorders, we assumed there might be relatively more specific CBC inflammatory markers when comparing substance‐related and substance‐free psychotic conditions, particularly for acute courses of illness.…”
Section: Introductionmentioning
confidence: 85%
“…A recent study showed that half of FEP patients had co‐occurring substance use disorders, and substance use has been repeatedly reported to contribute to the development of psychosis with adverse outcomes (Brunette et al, 2018; Kraan et al, 2016; Schoeler et al, 2016). Similarly, there are some reports that support the hypothesis that inflammatory pathways might be related to substance use disorders (Ozkan et al, 2017; Uys, Mulholland, & Townsend, 2014; Womersley, Townsend, Kalivas, & Uys, 2019). Considering previous findings that support the involvement of inflammatory pathways in both psychosis and substance‐related disorders, we assumed there might be relatively more specific CBC inflammatory markers when comparing substance‐related and substance‐free psychotic conditions, particularly for acute courses of illness.…”
Section: Introductionmentioning
confidence: 85%
“…Nötrofil/lenfosit oranı (NLO), Monosit/lenfosit (MLO) ve Platelet/lenfosit oranı (PLO) değerleri tam kan sayımı sonuçlarından manuel olarak hesaplanmıştır. Literatürde AKB ve MKB hastalarında inflamasyon belirteçlerinin incelendiği çalışmalarda elde edilen sonuçlar çelişkili olmuştur 14,16,20,21,[23][24][25][26][27][28][29] . Yapılan bir çalışmada alkol, sentetik kannabinoid ve eroin kullanım bozukluğu hastalarının NLO ve C-reaktif Protein (CRP) değeri karşılaştırılmıştır.…”
Section: Laboratuvar Incelemeleriunclassified
“…Yapılan bir çalışmada alkol, sentetik kannabinoid ve eroin kullanım bozukluğu hastalarının NLO ve C-reaktif Protein (CRP) değeri karşılaştırılmıştır. Elde edilen sonuçlarda üç hasta grubunun da; NLO sağlıklı kontrollerden yüksek olarak hesap edilmiştir 24 . AKB hastalarında NLO yüksekliğinin alkolik karaciğer hastalığı ve diğer alkol ile ilişkili komplikasyonlar ile bağlantılı olduğu bildirilmiştir 25 .…”
Section: Laboratuvar Incelemeleriunclassified
“…Yasa dışı ilaç bağımlısı kişilerde inflamasyonun ve inflamatuvar yanıtın arttığı görülmektedir (8). Güncel bir çalışmada yasa dışı ilaç bağımlılarında NLO kontrol grubuna göre arttığı ve inflamasyonu gösterdiği bildirilmiştir (23). Bizim çalışmamızda da NLO' nın NYS grubunda yüksek olduğu, bu yüksekliğin tedavi edilen hastalarda teda-…”
Section: Gereç Ve Yöntemlerunclassified